A family of receptor-like kinases are regulated by BES1 and involved in plant growth in Arabidopsis thaliana - Guo, Hongqing (Landes Bioscience, 2009)
Plant growth is dictated by both developmental and environmental cues, many of which are perceived by receptor-like kinases (RLKs). In Arabidopsis, there are more than 600 RLKs; but the functions of most of them are unknown. We recently found that several members of CrRLK1L family RLKs are regulated by plant steroid hormone Brassinosteroids (BRs). Two of the RLKs, FERONIA (FER) and THESEUS1 (THE1) have been previously found to inhibit cell elongation during pollen tube/synergid cell recognition and in sensing cell wall integrity after damage, respectively. However, we found that HERCULES1 (HERK1), another member in the family, as well as THE1 and FER, are regulated by BRs and required for cell elongation during vegetative growth. Here we provide additional evidence for the regulation of the family members by BR effector protein BES1. We also show that another member in the family, designated as HERCULES2 (HERK2), functions redundantly with HERK1 and THE1 to promote stem elongation. Our results, together with those from others, provide compelling evidence that the CrRLK1L family members play important role in plant growth.